Metaphoric Reading of the Poetry "Russian Nightmare" by Hossein Panahi based on Conceptual Blending Theory - Masoud Dehghan; Behnaz Vahabian (مطالعات زبانی و بلاغی)
The aim of this study is to examine the conceptual-cognitive metaphors of the poetry Russian Nightmares, fourth volume, from the seven-volume collection called Left Eye of Dog, written by Panahi 2010 based on Fauconnier and Turner's Conceptual Blending Theory (2002) (hencforth CBT) using mental spaces to describe the theory. They considered it as a special case of a more general and broader field. This broader variety is the analysis of mental mechanism when dealing with the conceptual domains. The authors of this study have examined the compositions and metaphors of Panahi's book known as "Russian Nightmares". The nature of the method of the present study was qualitative and the used method for analyzing the data was analytic-descriptive. The analyzed data has been chosen from his poets entitled Russian Nightmares. The examined and selected data are Panahi's poems, and the used tool is cognitive semantics, in particular CBT. The research results show that some used metaphors and compositions in these poems have created new spaces with the use of blending, composition, and completion so that it can make a new space in addition to source and target. In other words, the obtained results claim that Panahi has gone beyond conceptual metaphor theory (hencforth CMT) and he has used a higher model introduced as CBT with the use of which innovative and emotive metaphors have been discovered. Also, the research findings indicates the used metaphors by Panahi are from the type of double-space network.